The Biogas Plant From Liquid Waste Of Tapioca - Atmodjo M C T (Bandar Lampung University (UBL), 2017)
The Tapioca Plant has main product of Tapioca flour and Side Product Cassava Cellulose (onggok) and The Liquid Waste. The Biogas Plant is one of the best solution for Liquid Waste, The Liquid Waste of Tapioca plant needs integrated plant for waste application for us with circumstance friendly . There are two type of Biogas Reactor which one of the waste solution is CIGAR Type or Fixed Dome type. The Biogas yield collected in biogas tank which able to use for cooking stove and lamp for light. The liquid waste from Biogas Plant can be use for irrigation and the sludge able to use for fertilizer. The solid waste that has high content of cellulose and small amount of starch was dried several days and able to use for cattle or selling this solid waste to feed company